Sensitivity analysis of a moored floating offshore wind turbine using a CFD based surrogate model - Espinilla Soladana, Miguel (My University, 2021)
With increasing computational resources, the interest in high-fidelity simulations of wave-body interaction has increased. This is the case for the CFD modelling of Floating Offshore Wind Turbines (FOWT), as the industry moves towards commercial farms and the need for optimization increases. Previous computational models based on linear potential flow have shown a disagreement between the experimental and computational motions of the moored floaters subject to wave loading. The aim of this thesis is to help to clarify the influence of the mooring lines in this disagreement by performing a sensitivity analysis in the mooring line stiffness. A 1:50 scale model of a FOWT, defined by the OC5 project, is simulated using a coupled mooring analysis using CFD. The work uses OpenFOAM for the CFD part and Moody is used to model the mooring lines. The model is used to construct surrogate models for the floater motions and tensions in the mooring lines using Polynomial Chaos Expansion (PCE) in UQlab. The motions of the floater, the forces on the mooring lines fairleads and some flow characteristics are reported. It was found that for the wave case simulated the mooring stiffness had a negligible influence in the periodic motions of the floater, although it could affect significantly to the mean components of the mooring forces. The motions of the floater were found to be underpredicted with respect to the experimental data, but in agreement with simulations by other researchers.
Keywords: FOWT; Offshore wind; CFD; OpenFOAM; Moody; UQ; gPC; mooring